A small thing ... but big - Johnston, Tony, 1942- (Roaring Brook Press, 2016)
Lizzie meets an elderly man and his companion, Cecile, at the park, but Lizzie is afraid of dogs, so she relies on her new friend to help her take things one step at a time.